Capturing the Distance Learning in Indonesian Higher Education: Lecturers and Students’ Perspectives during Pandemic for Post-Pandemic - Arfive Gandhi; Prati Hutari Gani; Indra Lukmana Sardi (STAI Hubbulwathan Duri, 2023)
Since the pandemic, some universities can act swiftly to develop distance learning mechanisms, but others organize distance learning sporadically by allowing each lecturer to manage without standards. This research used a qualitative survey involving 66 students and 57 lecturers from various universities in Indonesia. It delivered dual perspectives between students and lecturers to improve previous research that did one perspective only. Most recognized the benefits of time and location flexibility when participating in distance learning but were dissatisfied with its implementation. During the pandemic, students were forced to explore independently by reading slides, listening to lecturers, watching videos, discussing in the online room, and doing independent assignments without any preparation. The pandemic also significantly changed the lecturers' teaching styles. They performed several variations in delivering material, increasing interaction in discussion forums, and evaluating the learning. Generally, distance learning without complete preparation since the pandemic was relatively good, as indicated by (1) lecturers' satisfaction with the course material delivery, (2) students' activeness according to the lecturer, and (3) learning outcomes achievement. These findings become insight for university stakeholders to enhance distance learning processes in the post-pandemic era since students and lecturers have felt its benefits but require many improvements.